Adult hemophagocytic lymphohistiocytosis causing multi organ dysfunction in a patient with multiple autoimmune disorders: when the immune system runs amok. Issue 2 (16th December 2015) - Fleischmann, Robert; Böhmerle, Wolfgang; von Laffert, Maximilian; Jöhrens, Korinna; Mengel, Annerose; Hotter, Benjamin; Lindenberg, Robert; Scheibe, Franziska; Köhnlein, Martin; von Bahr Greenwood, Tatiana; Henter, Jan Inge; Meisel, Andreas
Key Clinical Message: We report a case of several autoimmune disorders eventually presenting as severe multi organ dysfunction syndrome caused by adult hemophagocytic lymphohistiocytosis (HLH). Clinical and laboratory tests might lead to fatal misinterpretation without awareness of its diagnostic evaluation, as HLH shares common features with sepsis and immune‐mediated systemic inflammatory response syndromes. Abstract : We report a case of several autoimmune disorders eventually presenting as severe multi organ dysfunction syndrome caused by adult hemophagocytic lymphohistiocytosis (HLH). Clinical and laboratory tests might lead to fatal misinterpretation without awareness of its diagnostic evaluation, as HLH shares common features with sepsis and immune‐mediated systemic inflammatory response syndromes.